2018
DOI: 10.1371/journal.pone.0205149
|View full text |Cite|
|
Sign up to set email alerts
|

Antenatal care in rural Bangladesh: Gaps in adequate coverage and content

Abstract: IntroductionAntenatal care (ANC) has long been considered a critical component of the continuum of care during pregnancy, with the potential to contribute to the survival and thriving of women and newborns. Although ANC utilization has increased in over the past decades, adequate coverage and content of ANC contacts have fallen under increased scrutiny. The objectives of this article are to describe the coverage and content of ANC contacts in the context of rural Bangladesh.MethodsA community-based, cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 37 publications
6
54
0
7
Order By: Relevance
“…Consistent with other studies conducted in the context of rural Bangladesh, we found the coverage of ANC to be relatively low compared to the ambitious targets set at the global and national level (8,12,34,35). With less than one-tenth of women attending at least four ANC contacts, the global vision of women attending eight visits as proposed in the most recent WHO guidelines seem that it will be di cult to achieve in the near term (2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with other studies conducted in the context of rural Bangladesh, we found the coverage of ANC to be relatively low compared to the ambitious targets set at the global and national level (8,12,34,35). With less than one-tenth of women attending at least four ANC contacts, the global vision of women attending eight visits as proposed in the most recent WHO guidelines seem that it will be di cult to achieve in the near term (2).…”
Section: Discussionsupporting
confidence: 90%
“…It can reduce maternal and neonatal morbidity and mortality, and stillbirths through prevention, early identi cation and management of pregnancyrelated complications or pre-existing conditions (4)(5)(6). However, the quality of this care is often compromised in resource-scarce settings where women and newborns face the greatest risks to their health and well-being (7,8).…”
Section: Page 3/24mentioning
confidence: 99%
See 1 more Smart Citation
“…Antenatal care (ANC) provides a unique window of opportunity to ensure a healthy pregnancy through ensuring healthy weight gain and proper nutrition (e.g. intake of iron and folic acid), taking necessary immunizations packages such as tetanus toxoid and antimalarial drugs, controlling gestational diabetes, hypertension, and many other pregnancy related medical conditions [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Antenatal care (ANC) offers a distinctive platform that ensures a healthy pregnancy through; promotion of healthy weight gain and proper nutrition (e.g. intake of iron and folic acid), encouraging the uptake of necessary immunization packages such as tetanus toxoid and antimalarial drugs, controlling gestational diabetes, hypertension, and other pregnancy-related medical conditions [3][4][5]. Through ANC visits, pregnant women can easily follow up on the growth of the fetus, their own health including HIV status with focus on prevent mother-tochild transmission of HIV [6][7][8], a key contributor to childhood HIV in Africa [9,10].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%